Teachers' Strategies for Overcoming Learning Challenges in Fiqh Education at Ummu Fathimah Islamic Elementary School, Bengkulu City - Repaldo Rahmat Ilahi; Wildan Nur Hidayat; Nur Hidayat (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Fiqh learning in Integrated Islamic Elementary Schools (SDIT) holds high expectations for character building and worship practices, yet often faces a gap between curricular ideals and classroom realities. This study aims to analyze the problems and formulate comprehensive strategies of Fiqh teachers in improving students' religious understanding and value internalization at SDIT Ummu Fathimah, Bengkulu City. This study employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, participatory observation, and documentation, involving Fiqh teachers, the principal, the vice-principal of curriculum, and students as informants. Data validity was ensured through source and method triangulation, and analyzed using the Miles and Huberman interactive model. The results indicate that the main problems include students' difficulties in understanding abstract concepts, the dominance of conventional methods, and limitations in time allocation and facilities. To overcome these, teachers implement three synergistic strategies: (1) contextual strategies and simulation (role-playing) in the classroom to bridge abstract concepts; (2) integration of interactive audio-visual media optimized despite facility constraints; and (3) strengthening value internalization through structured habituation programs, such as congregational Dhuha and Dzuhur prayers, and recitation of selected Surahs. This study concludes that shifting the teacher's role from a mere instructor to a murabbi (nurturer) through exemplary behavior (uswah hasanah) and creating a conducive environment (bi'ah shalihah) is the key to bridging the cognitive and practical gaps in Fiqh learning.